Novel medications inducing adrenal insufficiency - Bornstein, Stefan R.; Bornstein, Tobias D.; Andoniadou, Cynthia L. (Nature reviews. Endocrinology, 2019)
Emerging evidence demonstrates that an increasing number of novel medications have considerable potential to induce adrenal insufficiency. This condition might lead to acute adrenocortical insufficiency, which is potentially fatal; however, the condition could be avoided if clinicians are more aware of the new findings and their implications.
Gesehen am 13.11.2019